A salvage chemotherapy of R‐P‐IMVP16/CBDCA consisting of rituximab, methylprednisolone, ifosfamide, methotrexate, etoposide, and carboplatin for patients with diffuse large B cell lymphoma who had previously received R‐CHOP therapy as first‐line chemotherapy. Issue 3 (21st March 2016) - Matsumoto, Takuro; Hara, Takeshi; Shibata, Yuhei; Nakamura, Nobuhiko; Nakamura, Hiroshi; Ninomiya, Soranobu; Kitagawa, Junichi; Kanemura, Nobuhiro; Goto, Naoe; Kito, Yusuke; Kasahara, Senji; Yamada, Toshiki; et al.
Abstract: We have reported the efficacy of the salvage chemotherapy P‐IMVP16/CBDCA for patients with diffuse large B cell lymphoma (DLBCL) who had previously received CHOP before the availability of rituximab (R). Here, we confirmed the efficacy of R combined with P‐IMVP16/CBDCA as a salvage chemotherapy for patients with DLBCL, who had previously received R‐CHOP. We retrospectively analysed 59 patients with relapse or refractory DLBCL (38 male patients and 21 female patients) presenting between June 2004 and June 2013. The patients received R 375 mg/m 2 on day 1, methylprednisolone 1000 mg/body for 3 days (from day 3 to day 5), ifosfamide 1000 mg/m 2 for 5 days (from day 3 to day 7), methotrexate 30 mg/m 2 on day 5 and day 12, etoposide 80 mg/m 2 for 3 days (from day 3 to day 5), and carboplatin 300 mg/m 2 on day 3 every 21 days. Patients aged 70 years or older were given 75% of the standard dose. The overall response rate (complete response + partial response) was 64.4%. The 2‐year overall survival rate was 55.3%. The 2‐year progression free survival rate was 34.7%. The 2‐year overall survival rate was 61.5% for the relapse patients, and 15.6% for the refractory patients ( p < 0.0001). One patient died because of sepsis related to the treatment regimen. Non‐hematological adverse effects were mild and tolerable. The R‐P‐IMVP‐16/CBDCA regimen displayed a significant activity in relapsed DLBCL, with acceptable toxicity, and should be considered a candidate for salvage chemotherapy. Copyright © 2016 John Wiley & Sons, Ltd.